Legal Basis and Prospects of International Cooperation Between Kazakhstan and China in the Field of Protection the Rights of Tourists (International relations and international law Journal, 2026)
The purpose of the study was to analyse the legal and regulatory framework and assess the possibilities for developing international cooperation between Kazakhstan and China to protect the rights of tourists. The study used a comparative analysis of legal acts, an analysis of intergovernmental agreements regulating the tourism sector, as well as a content analysis of reports of government agencies and industry associations. The paper examines the main mechanisms of legal regulation of tourist rights protection in Kazakhstan and China. The study analysed the effectiveness of existing institutional mechanisms of cooperation, in particular the functioning of the Kazakhstan-China Tourism Forum and joint border coordination groups operating under bilateral agreements. The study identified key problems, including insufficient coordination between national consumer protection authorities, the lack of a unified system for administrative review of tourist complaints, and difficulties with judicial settlement of disputes, which causes significant financial and time costs for tourists. It was found that a significant number of conflict situations are resolved through the mechanisms of self-regulation of the tourism business and out-of-court dispute resolution, in particular with the participation of industry associations and insurance companies. Prospects for cooperation were analysed, including the possibility of creating a single electronic database of tourist complaints between Kazakhstan and China, harmonizing travel insurance standards, and expanding alternative dispute resolution mechanisms, including international arbitration. Effective legal regulation of tourism activities is an important factor in the development of cross-border tourism and ensuring its sustainability, and the introduction of coordinated mechanisms for protecting the rights of tourists will help increase confidence in the tourism market and strengthen bilateral relations between Kazakhstan and China.Key words: legislation, regulations, liability, agreements, safety, cross-border travel